A novel approach to MP-PIC: Continuum particle model for dense particle flows in fluidized beds. (February 2020) - Verma, Vikrant; Padding, Johan T.
Graphical abstract: Highlights: A novel particle stress based continuum particle model (CFD-CPM) is developed. Newly developed CFD-CPM has an improved capability to simulate gas-particle flows. CFD-CPM is validated by comparing simulation results with literature (Lu et al., 2017 ). CFD-CPM has a high computational speed comparable to that of a MP-PIC model. Abstract: A novel approach to Multiphase-Particle-in-Cell (MP-PIC), called Continuum Particle Model (CPM), is developed for dense gas-particle flows. CPM has high computational speed, comparable to that of MP-PIC, but a robustness and accuracy closer to that of a Discrete Element Model (DEM). The gas phase is treated as a continuum phase and particles are tracked discretely, but particle collisions are modelled by considering the divergence of the continuum particle stress tensor. Details on efficient solution to the model are presented. For comparison, a parametric study is performed for quasi-2D fluidized beds. Comparison of CFD-CPM is made with MP-PIC and CFD-DEM. The particle stress models by Harris and Crighton, and by Srivastava and Sundaresan are tested in our CFD-CPM. Results from CFD-CPM based on the Srivastava and Sundaresan particle stress model show good agreement with CFD-DEM results. We validate our model by comparison with experimental benchmark results from Gopalan et. al. (2016).